2015
DOI: 10.1080/1745039x.2015.1073001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation of rumen-protected choline on growth performance, meat quality and gene expression inlongissimus dorsimuscle of lambs

Abstract: This study determined the effects of rumen-protected choline (RPC) on growth performance, blood lipids, meat quality and expression of genes involved in fatty-acid metabolism in young lambs. A total of 24 Dorper × Hu lambs (about 20 kg body weight) were kept in individual pens and fed diets with 0%, 0.25%, 0.50% and 0.75% RPC for 60 d. Supplementation of 0.25% RPC increased average daily gain of lambs, whereas treatments had no significant effect on feed intake. The pH values of meat were increased at 0.25% RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
56
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 29 publications
14
56
8
Order By: Relevance
“…However, it resulted in lower drip loss, cook loss and shearing force, thus exhibiting a tendency to improve meat quality. This is consistent with the findings of Li et al (2015). Choline occurs in the cell membranes as lecithin, and improves the structural integrity of cell membranes, thereby enhancing meat quality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, it resulted in lower drip loss, cook loss and shearing force, thus exhibiting a tendency to improve meat quality. This is consistent with the findings of Li et al (2015). Choline occurs in the cell membranes as lecithin, and improves the structural integrity of cell membranes, thereby enhancing meat quality.…”
Section: Discussionsupporting
confidence: 92%
“…China, it was shown that dietary supplementation with 0.25% RPC can promote weight gain in young lambs and improve meat quality (Li et al, 2015). In a subsequent study conducted in Egypt during summer it was found that RPC supplementation at 20 g/buck/day in growing male Zaraibi goats under heat stress yielded the best growth performance, feed conversion and blood metabolite levels, and economic efficiency (Habeeb et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, some metabolites (triglycerides and NEFA) were affected at a dose of just 6.42 mg/kg BW 0.75 , but Li et al (2015) did not find any such effects in blood cholesterol and triglycerides in lambs receiving an estimated dose from 37 to 116 mg/kg BW 0.75 . In dairy cattle, Pinotti et al (2004) observed a significant increase of plasma cholesterol and a NEFA decrease with a tendency for increased glucose with an estimated effective duodenal dose of 75 mg/kg BW 0.75 .…”
Section: Fermentation Gas Parametersmentioning
confidence: 92%
“…The relationship between gluconeogenic factors and methylation affected by nutrition levels (Rattanatray et al, 2014) deserves more attention in ruminant studies. The RPC, when given at lower doses (Li et al, 2015), stimulated the expression of lipoprotein lipase and fatty-acid synthase genes in muscle, but at higher doses, it showed adverse effects on the expression of some acetyl-CoA carboxylase genes. Future studies with both choline and Met that consider the gene expression of key liver enzymes and their regulating factors are required to understand the regulation of cholesterol in ruminants (Viturro et al, 2009).…”
Section: Fermentation Gas Parametersmentioning
confidence: 99%
“…Ruminally protected choline chloride has been the most frequently evaluated source of choline for small ruminants (Bryant et al, 1999;Godinez-Cruz et al, 2015;Tsiplakou et al, 2016;Habeeb et al, 2017), and doses above 2.5 g/kg DM, equivalent to an intake of over 3 g/d for lambs, showed adverse effects on lamb performance (Li et al, 2015). However, the causes of the impaired performance have not been identified.…”
Section: Introductionmentioning
confidence: 99%